Implementasi Program Keluarga Harapan (PKH) Di Kecamatan Binongko Kabupaten Wakatobi - La Ode Muhammad Elwan (Journal Publicuho, 2018)
Poverty reduction is an issue that should be resolved by the Government to soon completed and disconnected the chain of causes. Poverty reduction is currently oriented material so its sustainability depends greatly on the availability of the budget and the Government's commitment. The policy measures were undertaken by the Government to abolish it one is the family Program expectations. Welfare is the ultimate goal of the Family Expectations Program, namely to improve the quality of life of the family is very poor with access to health services and education. With the unsettled Family, Hope Program is expected to improve the social life of economy, education and public health, especially in poor community groups. The purpose of this study is to describe the implementation of a programme of Family expectations, find supporters and restricting factors and efforts to overcome it in the Wakatobi Binongko. Theory approaches used in this research is policy implementation approach Daniel Mazmanian and Paul Sabatier. The theory sees variables easy to control, the issue of whether or not the variable policy capabilities in the implementation process to manage appropriately and the variable outside the policies that affect the process of implementation. The research method used is descriptive research methods with qualitative approaches. Data collection was done through observation and interview. Research results showed the Family Hope Program Implementation in district Binongko Wakatobi many experience obstacles and have not been implemented properly. Socialisation has not been comprehensive so that less had the support of the parties concerned. It captures the recipient's Family Hope Program participants is not yet comprehensive, there are still many who have not to get family Program expectations. This has not been done well and the use of funds the Program Families Hope by very poor Households often used outside the conditions. For the long term cannot change the mindset and behaviour of very poor Households significantly.    Keywords: Implementation Of Policy, Family Expectations Program